Analysis of the cement clinker produced with incorporation of petroleum sludge - Benlamoudi, A. (Institute of Physics Publishing, 2018)
Very limited researches have been conducted on the incorporation of petroleum sludge waste into cement clinker production even though this waste may contain similar components to those of clinker raw materials. In this research, petroleum sludge was integrated into cement plant as raw material to produce the cement clinker. As results, incorporation of 5 of this waste was able to produce an acceptable quality of cement. Despite the use of petroleum sludge has decreased the properties of the produced clinker, but it still fit the requirements. Â© 2018 Institute of Physics Publishing. All rights reserved.